Systemic argyria with severe anemia (hemoglobin 2.4 g/L). Issue 3 (4th May 2022) - Chow, Nathan; Fain, Kristen; Truitt, Jay; Stetson, Cloyce
Abstract: Argyria is a rare disease in which chronic usage of products with a high silver content leads to deposition of silver granules in organs such as the skin, resulting in a permanent blue-gray discoloration. We present a 68-year-old woman with a 10-year history of chronic anemia of unknown etiology who was admitted for progressive generalized weakness, dyspnea, and a widespread slate-gray tint to her skin. She had previously consumed 1 tablespoon per day of colloidal silver orally for 7 years. Hematologic workup on admission showed the hemoglobin to be 2.4 g/dL with low ferritin and normal copper, zinc, and ceruloplasmin, indicating an iron-deficiency anemia. Differentiating the correct etiology of her anemia and skin discoloration was crucial since argyria can cause pseudocyanosis and microcytic anemia secondary to silver-induced copper deficiency. This case highlights the importance of asking and counseling patients about their nonprescription supplements.